Structural, magnetic, grain and grain boundary mediated conduction features of low dimensional LaFeO3 nanoparticles. (10th June 2019) - Lakshmana Rao, T; Pradhan, M K; Chandrasekhar, M; Ramakrishna, P V; Dash, S
Abstract: A detailed investigation of crystal structure, magnetic and electrical conduction properties of a low dimensional LaFeO3 is reported. The sample is synthesized by Sol-Gel method with a low preparation temperature. Synchrotron x-ray diffraction, Raman and FTIR spectroscopy methods were used to establish the structural phase and vibrational modes present in the sample. The low dimensionality and morphology of the prepared sample is probed through transmission electron microscopy. From the explicitly field and temperature dependent magnetization, the magnetic phase exhibited by the nanoparticle is weak ferromagnetic which is further evidencing from the Fe 57 Mossbauer spectroscopy. To gain further understanding of electrical conduction mechanism and related features of AC conductivity, impedance spectroscopy techniques are used. It is noticed that, the grain effect is dominated while the electrode effect is suppressed with temperature. The activation energies due to grain and grain boundary effect are found to be 0.0780 eV, 0.175 eV for T < 90 °C and 0.451 eV, 0.525 eV for T > 90 °C respectively. Finally, jump relaxation model and Jonscher's power law are used to explain the frequency-dependent conduction behavior in the system.